Effectiveness of Interventions Co-Financed by the EU Structural Funds in Wielkopolska in the Years 2004-2006 - Churski, Paweł; Borowczak, Anna (Quaestiones Geographicae, 2010)
The aim of this article is to analyse the effectiveness of interventions from the EU Structural Funds in Wielkopolska carried out for investments realised in the years 2004-2006, i.e. in the first period of implementing Community regional policy in Poland. The research procedure is composed of two fundamental stages. In the first, projects co-financed from the EU Structural Funds within the framework of the Regional Component of the Integrated Regional Operational Programme were systematised by the criterion of intervention direction within each of the three dimensions of cohesion: economic, social and territorial. In the second stage, selected diagnostic measures for each dimension of cohesion were subjected to effectiveness analysis. The procedure rested on a questions/methods-oriented model applied in line with the theory-driven evaluation approach, a quasiexperimental design and the difference-in-differences technique, as well as methods of econometric analysis. The results made it possible to assess public intervention in Poland in terms of its effectiveness, and to identify challenges that have to be faced very soon.